Effect of Utilization of Bamboo Fiber and Gypsum Substitution as Cement Against Strong Concrete Press - Daniel Rizsky Tambunan; Acep Hidayat (Journal of World Conference (JWC), 2021)
Bamboo Fiber is one of the materials that can be alternative as an added material to increase strong concretepress. The gypsum waste comes from the disposal of household flatfon dismantling, which becomes one of the added materials in the manufacture of cement. The use of both materials as concrete mixture subtitution is expected to reduce environmental pollution and exploitation of natural resources. This research aims to find out the influence of the use of SB as fiber and LG as cement subtitution semen on concrete mixture against strong concrete press. The study used a mixture of SB of 1%, 1.5%, 2%, and 3%of cement weight, as well as LG as much as 3%,and5% of cement weight. Strong press testing was conducted on the 14th and 28th days. The result of this study is that the higher percentage of SB and LG workability is decreasing. Strong press testing shows that all variations have a strong press yield of 1%B3%G above the normal concrete press strength and the rest under normal concrete. The highest press strong value is derived from the variation of 1%B3G with a mixture of 1%SB + 3% LG which is 20.81 MPa.